Implementasi Penerapan Disiplin Kerja Pegawai Negeri Sipil Dinas Kesehatan Di Kabupaten Kotawaringin Barat Berdasarkan Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Peraturan Disiplin Pegawai Negeri Sipil - admin, admin; Saragih, Medy Oktalina; Biroum R, Raden; Lion, Eddy (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2022)
Public service is the government's effort to improve the welfare of the community as well as to improve the quality and capacity of carrying out the duties and functions of government institutions. The purpose of this study is to describe and analyze the implementation of the application of the rules of discipline for Civil Servants at the Health Office of West Kotawaringin Regency. This research use desciptive qualitative approach. Data collection in this study was carried out through observation, interviews, documentation and data triangulation. Checking the validity of the research data was carried out in three ways, namely member check, data triangulation and method triangulation. The data analysis model used in this study uses the Miles and Hubermen interactive model with three components of analysis, namely Data Reduction, Data Presentation and Conclusion Drawing. The result of this research is that the implementation of Government Regulation No. 53/2010 in the Health Office of West Kotawaringin Regency needs cooperation and commitment from all parties, especially the leaders of the Health Office and employees.